Design of an Arduino Mega-Based Walking Cane Assistive Device to Improve the Quality of Life for the Elderly in the Riau Islands Province - Dimas Akmarul Putera; Aulia Agung Dermawan; Dwi Ely Kurniawan; Alvendo Wahyu Aranski; Rafi Dio (Scientific Journal of Informatics, 2023)
Purpose: The number of people aged 60 or older is expected to increase globally by nearly three times from 737 million in 2009 to 2 million by 2050. Indonesia's population is projected to reach 28 million by 2045, making up nearly one-third of the total population. In 2020, the population aged 60 or older reached 29.52 million, with 29.52 million from the last two houses being occupied by a house due to numerous housing programs that require a close relationship between people. The study suggests that a house with a strong sense of belonging is a risky group required attention. The study uses a smartphone with a 180° panorama camera and GPS to help locating the house and performing its activities.Methods: Anthropometry can be defined as the study of body dimensions, namely body size, shape, strength and work capacity for the purpose of body design and composition and prototyping. Results: This research has resulted in elderly sticks that use sensors to help elderly mobility. This stick can detect the environment nearby the ESP32-Cam with the password "/Capture_photo" and is able to send information about the location of the elderly by sending a message to the GSM Number connected to the Arduino Mega with the password "Hello" and the device will send a message containing the location of the elderly.Novelty: Based on previous research reviewed by researchers, it was found that similar research using Camera and GPS Technology to Improve the Quality of Life of the Elderly has not been carried out in the Riau Islands of Batam.